WOMEN AND NATIONALISM IN INDONESIA - Pohlman, Annie (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Indonesia was established 65 years ago, but the progress of Indonesian nasionalism had not yet done when the independence was proclaimed. The nationalism movement in Indonesia has been growing since the early of the 20th century until today because nationalism is not static but it always changing. In the nationalism development process, women always play the basic and important role. However, in many academic discourses discussing the nationalism history, women are neglected most of the time. Women participation in the nationalism movement is rarely discussed. The gender relation and its association with the development of Indonesia development are also neglected most of the time. Therefore, women role in the nationalism movement and the women interest tend to be removed. However, women always play the central role in the nationalism movement, such as in the beginning of the 20th century, during the colonialism government and Japanese era, the Revolution era against the Dutch, and the regime of Soekarno and Soeharto era. In this article, I will focus my discussion on the women movement development since the 1920s and their role in the Reformation movement and Indonesia nationalism. This article will discuss: (1) the first discussion starts with the summary of the women movement and nationalist movement background in the twentieth century; (2) the second discussion is about the development of women movement in the Reformation era; and (3) finally, I will explore some issues that affect the discussion of the women and nationalism in the Reformation Era – the Indonesian nationalism developed by the Government utilizing the women’s body and sexuality for achieving their goal is the central issue in the discussion about the form of Indonesia nationality.